PENERAPAN STRATEGI INKUIRI BIOLOGIUNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IIISD NEGERI 010 SILIKUAN HULU KECAMATAN UKUIKABUPATEN PELALAWAN - ', Sungkem (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this research problems is the low result of third grade students learn science. It is characterized by the acquisition of an average value of 59.50 Science learning outcomes with students learning completeness percentage of 45%.. Based on this the researchers conducted a classroom action research (PTK) with the aim to improve student learning outcomes through the implementation of strategies IPA biological inquiry. This study was conducted in SD Negeri 010 Silikuan Hulu Kecamatan Ukui. The subjects were students of class III with a number of 15 students with details of nine boys and six girls. The study was conducted by two cycles consisting of 2 meetings and a daily test at the end of each cycle. Data collection techniques in this study is the observation technique teacher and student activities and engineering test, while the analytical technique used is descriptive analysis of activity data and the results of teachers and students learn science. Research suggests that the application of biology inquiry strategies to improve learning outcomes IPA. This is evidenced by: (a) the activities of teachers and students has increased in each cycle, the activities of teachers in the first cycle the first meeting obtained by percentage of 42%, the first cycle of meetings both gained 52%. The first meeting of the second cycle gained 65% and in the second meeting of the second cycle was obtained by 78%. Activities of students in the first cycle the first meeting obtained by percentage of 49%, student activities at the second meeting I silus 61% and the second cycle first meeting obtained by percentage of 68% and the second cycle of the second meeting obtained by percentage of 81%. (B) the results of the students' learning experience at each cycle, before the action is complete learn student by 45% with an average value of 59.50. First cycle increased to 72% with an average value of 64. The second cycle increased to 90% with an average of 68.